Reversing the Negative Genomic Effects of Aging with Short-Term Calorie Restriction - Stephen R. Spindler (The Scientific World Journal)
According to government figures, total health care spending in the U.S. in 1999 was $1.316 trillion. The government projects an increase in health care costs to $2.176 trillion by 2008. If we project this growth rate to 2020, health care costs will reach $4.009 trillion. Today, people often spend more health care dollars during the last year of their lives than in all previous years combined. Medical treatment in the last few years of life is usually very expensive and often futile. With the baby-boom generation now moving through middle age, the prescription for the U.S. health care system will be disastrous unless we learn how to keep people healthier longer. This dramatic increase in health care costs leaves us with only one acceptable alternative to rationed health care or financial ruin — to discover interventions that make people functionally younger, healthier, and less susceptible to debilitating, age-related diseases.